ADDITION OF PROPIONIC ACID ON NUTRIENT DIGESTIBILITY AND ITS EFFECT ON PRODUCTION AND CARCASS QUALITY OF BROILER - Palupi, R.; Lubis, F. N. L.; Suryani, A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to determine protein and crude fiber digestibility by adding propionic acid in rations and its effect on production and carcass quality broiler chicken. This research was carried out using 180-day old chicks (DOC) broiler chicken with Cobb strain. This research method used a completely randomized design (CRD) consisting of three treatments and six replications for every treatment. The treatment in this study consisted of: T0 = ration without propionic acid; T1 = addition of 0.5% propionic acid in the ration; T2 = 0.75% addition of propionic acid in the ration. Parameters observed included crude protein, crude fiber digestibility, feed consumption, body weight gain, feed conversion, live weight, carcass percentage, and percentage of abdominal fat in broiler chickens. The results showed that the addition of 0.5% propionic acid had a significant effect (P<0.05) on crude protein and crude fiber’s digestibility in broiler chickens. Significantly increased feed consumption up to 2.29%; body weight gain up to 7.49 %, decreased feed conversion by 4.86%; increased body weight by 12.69%; carcass percentage by 4.12% and decreased 33% of abdominal fat broiler chicken. This research concludes that the addition of propionic acid in the ration at a dose of 0.5% could be increase the digestibility of crude protein and crude fiber rations, can improve the production performance and carcass quality of broiler chickens.